2016
DOI: 10.1016/j.annepidem.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Population impact of preterm birth and low birth weight on developmental disabilities in US children

Abstract: Purpose Although previous studies demonstrate associations between adverse perinatal outcomes and developmental disabilities (DDs), study of population impacts is limited. Methods We computed relative risks adjusted (aRRs) for sociodemographic factors and component and summary population attributable fractions (PAFs) for associations between very low birth weight (VLBW, all preterm births), moderately low birth weight (MLBW) + Preterm, MLBW at term, and normal birth weight (NBW) + Preterm and seven DDs (cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(105 citation statements)
references
References 37 publications
(44 reference statements)
6
95
0
4
Order By: Relevance
“…Similar considerations can be done for studies with ELBW (<1 kg) subjects, although in this case the sample sizes are even smaller than in the case of VLBW (Hack et al., ; Szatmari et al., ; Van Lieshout et al., ). Of note, three papers (Breeman et al., ; Jaekel et al., ; Schieve et al., ) considered the combination of VP and VLBW as a risk factor for ADHD, but the effect size range (0.25–0.56) was smaller than that of the studies considering only VLBW. However, two of these studies (Breeman et al., ; Jaekel et al., ) showed a specific association with ADHD‐IA: the cumulative effect of multiple risk factors might be associated with specific ADHD subtypes, respectively (2.8; CI: 1.6–5) (RR: 2.76; CI: 1.46–5.19).…”
Section: Discussionmentioning
confidence: 99%
“…Similar considerations can be done for studies with ELBW (<1 kg) subjects, although in this case the sample sizes are even smaller than in the case of VLBW (Hack et al., ; Szatmari et al., ; Van Lieshout et al., ). Of note, three papers (Breeman et al., ; Jaekel et al., ; Schieve et al., ) considered the combination of VP and VLBW as a risk factor for ADHD, but the effect size range (0.25–0.56) was smaller than that of the studies considering only VLBW. However, two of these studies (Breeman et al., ; Jaekel et al., ) showed a specific association with ADHD‐IA: the cumulative effect of multiple risk factors might be associated with specific ADHD subtypes, respectively (2.8; CI: 1.6–5) (RR: 2.76; CI: 1.46–5.19).…”
Section: Discussionmentioning
confidence: 99%
“…The term cerebral palsy (CP) covers a group of permanent disorders of movement and posture, and various behavioural, emotional, [1][2][3] or psychiatric disorders [4][5][6][7] have been described among children with CP. 13 Other hypotheses, including recent extensive progress in genomic sequencing, raise the hope of major advances in knowledge of these disorders. 5,[8][9][10][11][12] It has been suggested that several developmental disorders including CP, ASD, and also attention-deficit-hyperactivity disorder (ADHD) may share common underlying causes such as perinatal risk factors.…”
mentioning
confidence: 99%
“…Согласно данным зарубежных авторов, распространен-ность ДЦП характеризуется вариабельными по-казателями с максимальным значением 15-30% в группе детей, рожденных ранее 28 нед, 6,2% -среди тех, кто родился на сроке гестации 28-31 нед, 0,7% -на сроке 32-36 нед и 0,1% -сре-ди доношенных детей [4]. Подобные результаты были продемонстрированы и Schieve L.A. et al в 2016 г., согласно которым новорожденные с массой тела при рождении менее 1 500 г ассо-циированы с 43-кратным увеличением вероятно-сти развития ДЦП (ОШ = 43,5; р < 0,05), дети с массой тела 1500-2500 г с 10-кратным риском (ОШ = 10,1; р < 0,05) [5]. Также авторы отме-чают, что повышение риска развития ДЦП ре-гистрируется при многоплодной беременности: частота ДЦП в случае наличия одного плода со-ставляет 0,2%, при двойне -1,5%, при тройне -8,0%, при четырехплодной беременности -43% [4,5].…”
Section: характеристика нарушений центральной нервной системыunclassified
“…Подобные результаты были продемонстрированы и Schieve L.A. et al в 2016 г., согласно которым новорожденные с массой тела при рождении менее 1 500 г ассо-циированы с 43-кратным увеличением вероятно-сти развития ДЦП (ОШ = 43,5; р < 0,05), дети с массой тела 1500-2500 г с 10-кратным риском (ОШ = 10,1; р < 0,05) [5]. Также авторы отме-чают, что повышение риска развития ДЦП ре-гистрируется при многоплодной беременности: частота ДЦП в случае наличия одного плода со-ставляет 0,2%, при двойне -1,5%, при тройне -8,0%, при четырехплодной беременности -43% [4,5]. В Российской Федерации заболеваемость ДЦП составляет в среднем 4-5 случаев на 1 000 новорожденных, что превышает статистические показатели многих других стран [6].…”
Section: характеристика нарушений центральной нервной системыunclassified